Revitalisasi Identitas Diri Komunitas Masjid Saka Tunggal Banyumas, Masjid Raya Al Fatah Ambon, dan Masjid Agung Jami’ Singaraja Bali dalam Perubahan Budaya Global - Salehudin, Ahmad (Religió: Jurnal Studi Agama-agama, 2018)
This study examines how three communal mosques: Masjid Saka Tunggal Cikakak Banyumas, Masjid Raya Al Fatah Ambon, and Masjid Agung Jami’ Singaraja respond toward globalization. Globalization that is characterized with the territorial demarcations of states’ administration jurisdiction, political currents, economic strata, and religions has shaped global villages with cultural homogeneity as its estuary. Strong cultures tend to crush the vulnerable cultures. These conditions tend to generate a dilemma for the existence of an identity, including the identity of communal mosques. However, communal mosques are not merely a set of inanimate objects which can only passively accept external influences. They are a collection of beings who “tactically” respond to the “strategy” of the global cultural cooptation. The result of this study reveals that communal mosques become a collective awareness of each its individual to respond to and live the life amidst the increasingly uncontrollable wave of global cultures. Global cultures, as long it benefits, are adapted and adopted to strengthen their communal identity and, otherwise, left when they bring disadvantages. In order to protect communal identities, the result of this study offers three ways: habituation and institutionalization of the communal identity, reinforcing the ancestral authority, and affirming the institutional vision and mission. [Penelitian ini mengkaji respon tiga komunitas masjid, yaitu Masjid Saka Tunggal Cikakak Banyumas, Masjid Raya Al Fatah Ambon, dan Masjid Agung Jami’ Singaraja terhadap globalisasi. Globalisasi yang ditandai oleh menghilangnya batas-batas administrasi negara, aliraan politik, strata ekonomi, dan agama telah membentuk kampung global dengan homogenisasi budaya sebagai muaranya. Budaya yang kuat cenderung menggilas budaya yang lemah. Kondisi ini cenderung melahirkan dilema bagi eksistensi identitas, termasuk identitas komunitas masjid. Namun demikian, komunitas masjid bukanlah sekumpulan benda mati yang hanya bisa pasrah menerima pengaruh luar, tetapi sekumpulan mahluk hidup yang “taktik” untuk merespon “strategi” kooptasi budaya global. Hasil penelitian menunjukkan masjid-masjid komunitas menjadi collective awareness para individu untuk merespon dan menjalani kehidupan di tengah samudra budaya global yang semakin tak terkendali. Budaya global diadaptasi dan diadopsi selama bermanfaat untuk menguatkan identitas komunitasnya, dan bersikap acuh jika tidak sesuai atau membahayakan. Untuk melindungi identitas komunitasnya, ada tiga hal yang dilakukan, yaitu melalui pembiasaan dan pelembagaan identitas komunitas, meneguhkan otoritas leluhur, dan peneguhan visi misi lembaga.]